EVALUATION OF EFFICACY, INTRAUTERINE SAFETY AND STORAGE CONDITIONS OF LUGOL’S IODINE - SOOD, PANKAJ; THAKUR, S D; SARVESH; DOGRA, V; VASISHTA, N K; SINGH, M M; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2023)
Different concentrations of Lugol’s iodine [I 2KI] have been utilized to treat endometritis with variable success rates in cows. In present study, intrauterine infusion of 30 ml of 0.3% I2KI during estrus and one day later revealed a therapeutic success rate of 56.2% in 16 cycling cows with moderate moderate/severe clinical endometritis. The cows not responding tended to have a greater magnitude of uterine microbial load before treatment. The same protocol investigated in another set of six cows with healthy uterus revealed a normal endometrial histology in the estrus succeeding l2KI infusion, thereby suggesting the said protocol to be safe .. In another part of study, I2KI stored in transparent or dark glass containers for a period of 6 months and exposed to illumination intensity of 69.5 ± 2.3 lux did not affect the in vitro antibacterial activity. However, an air exposure for 72 h significantly reduced the optical density and in vitro antibacterial activity.